Aethes rutilana - Budashkin, Yuriy; Richter, Ignác (Zenodo, 2021)
Aethes rutilana (Hübner, [1817]) Material examined. 2♂, Montenegro. Bjelasica Mts., Crna glava, 25.vi.2012. 2♂, North Macedonia. Pelister Nacional Park, Golemo jazero, 1.viii.2015; 2♂, 1♀, Pepelište near Negotino, 13.iv.2019 and 21.iv.2019. Distribution. Europe, Russia (Kaliningrad region, Kola Peninsula, European Northwest region, European Northeast region, Central part of the European Russia, European south taiga region, Volga–Don region, Middle Volga, Ural, Siberia) (Hübner 1796 –1836; Razowski 1970, 2002, 2009; Kuznetzov 1978; Sinev et al. 2019). : Published as part of Budashkin, Yuriy & Richter, Ignác, 2021, New records of Cochylini moths (Lepidoptera: Tortricidae) from the Balkans, pp. 441-456 in Zootaxa 5082 (5) on page 447, DOI: 10.11646/zootaxa.5082.5.3, http://zenodo.org/record/5796363 : {"references": ["Hubner, J. (1796 - 1836) Sammlung europaischer Schmetterlinge. Horde 7. Tortrices. Privately published, Augsburg, 53 pls.", "Razowski, J. (1970) Cochylidae. In: Amsel, H. G., Gregor, F. & Reisser, H. (Eds.), Microlepidoptera Palaearctica. 3 (Part 1 - Part 2). Georg Fromme & Co., Wien, pp. vii - xiv + 1 - 528 & pls. 1 - 161.", "Razowski, J. (2002) Tortricidae (Lepidoptera) of Europe. Vol. 1. Tortricinae and Chlidanotinae, F. Slamka Publ., Bratislava, 247 pp.", "Kuznetzov, V. I. (1978) 21 Sem. Tortricidae (Olethreutidae, Cochylidae) - listovjertki. In: Medvedev, G. S. (Ed.), Opredelitel' nasekomyh evropejskoj tchasti SSSR. 4 (1). Nauka (Leningradskoje otdelenie), Leningrad, pp. 193 - 710. [in Russian]", "Sinev, S. Yu., Nedoshivina, S. V. & Dubatolov, V. V. (2019) Tortricidae. In: Sinev, S. Yu. (Ed.), Catalogue of the Lepidoptera of Russia. 2 nd Edition. Zoological Institute RAS, St. Petersburg, pp. 120 - 156. [in Russian]"]}